Integrating strength, speed, and endurance: a comprehensive training model for 100m and 400m sprints - YAO WU (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Sprint performance in the 100m and 400m events depends on an optimal balance of strength, speed, and endurance. Traditional training often isolates these components, whereas an integrated approach may yield superior performance adaptations.